(untitled) (Web of Teachers: Inderscience Research, 2025)
The rise of the field of Informatics and the rapid development of digital technologies in the present time directly and indirectly affect all aspects of human life. Along with the development of Information Technology, the concept of artificial intelligence began to develop on a large scale. Artificial intelligence is important in the manifestation of certain functions of human thought with the help of machines and programs. Today, the formation of a knowledge society, the widespread use of modern digital technologies and “smart” systems in our lives shows how relevant artificial intelligence is.